Historiografia e epistemologia no campo da Ciência da Informação: um olhar sobre a literatura brasileira - Silva, Tiago José da (2019)
This thesis research investigates the scientific production about the Epistemology and Historiography of Information Science from the communications of Encontro Nacional de Pesquisa em Ciência da Informação (ENANCIB), datas from Plataforma Lattes and the indexed literature in the Base de Dados da Ciência das Informação (Brapci). It identifies the collective of researchers who provide support, continuity and consistency to the epistemological and historiographic works of the area. It describes the context of creation and development of Information Science from the scientific communications of researchers in this field. It verifies the literary relations between the these teachers. It works on the concepts of the epistemology and historiography of Information Science, referring to the established authors of this domain. To do so, it uses the index method proposed by Ginzburg (1989) and Araújo's technique of brauseio (1994). The techniques of the metric studies of the information developed in the area are also applied, to rank and translate the indications of the production and communication of the area. In this area, a small group can produce more than most researchers. The results indicate that collaborative relationships in articles are made, most of the times, from the guiding and guiding relationship. Researchers with graduate students tend to publish more articles in collaboration than other authors who do not fit this profile. Most strictu sensu graduate research projects have mostly worked on the subject matter on the screen. The results allowed the description of the profiles of researchers from a clipping. It concludes that the research on this subject aligned with the precepts of the metric studies can allow the development of conceptual and methodological webs of Information Science.